“Degradación ambiental y crecimiento económico: un análisis de datos panel para América Latina durante el periodo 1961 – 2016” - Masache Tandazo, Jorge Eduardo (2021)
The environmental situation in Latin America is quite worrying, since human economic activities are causing the degradation of ecosystems, leading to the loss of 18.5% of biodiversity. In this context, this research examines the effect of economic growth on the levels of environmental degradation, for Latin America during the period 1961 - 2016. Seventeen countries are analyzed with data obtained from the World Bank's World Development Indicators (WDI) database (WB, 2019) and the Global Footprint Network (GFN, 2019). Panel data econometric techniques such as a Generalized Least Squares (GLS) model, Westerlund cointegration techniques for the long run and FMOLS were used to test the elasticity of variables in equilibrium in the long run and finally the panel Granger-type causality test of Dumitrescu and Hurlin (2012) was used. The results obtained show a positive and significant relationship between the ecological footprint, carbon dioxide emissions and economic growth. There is cointegration of all the variables in the long term and a bidirectional causality between the ecological footprint and the GDP per capita in general. Similarly, a unidirectional causality was found between the ecological footprint and GDP per capita for the LMIC panel and a unidirectional causality between carbon dioxide emissions and GDP per capita for all groups of countries.